Impact of biocontrol on the seed regenerative capacity of Lantana camara L. (sensu lato) (Verbenaceae). Issue 6 (3rd June 2022) - Katembo, Naweji; Simelane, David; Byrne, Marcus; Witkowski, Ed T.F.
ABSTRACT: The combined impact of biocontrol agents on the seed regenerative capacity, i.e. seed production, seed-rain, soil seedbank, seed germination and seedling density, of Lantana camara L. ( sensu lato ) (Verbenaceae), was measured in the field in an inland area of South Africa. The study was conducted on 10 plots (20 × 50 m each) along part of the Sabie River catchment. The most prevalent biocontrol agents at the site were Aceria lantanae (Cook) (Acari: Trombidiformes: Eriophyidae), Hypena laceratalis Walker (Lepidoptera: Noctuidae), Octotoma scabripennis Guérin-Méneville (Coleoptera: Chrysomelidae), Ophiomyia camarae Spencer (Diptera: Agromyzidae) and Teleonemia scrupulosa Stål (Hemiptera: Tingidae). Using the insecticidal exclusion method, comparisons of seed regenerative capacity were made between exclusion (insecticide treated) and biocontrol (untreated) plants over a three-year period. Lantana camara seed production per plant was slightly lower in biocontrol (5831 ± 844 seeds) compared to exclusion plants (6718 ± 1571 seeds), seed-rain density was significantly lower in biocontrol (1080 ± 122 seeds m −2 ) compared to exclusion plants (1419 ± 154 seeds m −2 ). Seed germination was lower in biocontrol (98 ± 41 seeds m −2 ) compared to exclusion plants (116 ± 38 seeds m −2 ). Seedling density was higher in biocontrol (36 ± 14 seedlings m −2 ) compared to exclusion plants (32 ± 11 seedlings m −2 ). Adult plants appeared to suppress their own seedlings. This study showed that the impact of the current suite of biocontrol agents on the recruitment potential of L. camara is minimal, emphasising the need for additional agents, better adapted to the cooler high altitude inland environmental conditions.